Creative teaching strategies in history effects on pupil achievement and attitude - Madrid, Marieta S. (2009)
This study aimed to develop teacher exemplars using creative teaching strategies to enhance pupil achievement and attitude in history. Two Grade 4 sections of Placido Del Mundo Elementary School were taught using creative teaching strategies (experimental) and the conventional way (control). HKS4, lesson exemplars, and survey attitudinaire. The results of the posttest and attitudinaire showed that pupils taught using creative teaching strategies gained more knowledge and positive attitude than those using the conventional way. The lesson exemplars were excellent in terms of objectives, content, learning activities , creative teaching strategies, and evaluation. Teachers as agents in promoting quality education need to be updated and well informed about the changes and innovations in the teaching profession. They should spearhead the quest for more appropriate and challenging teaching strategies to develop students' creativity and problem-solving skills and develop in them the courage to achieve what they want in life. With this notion, this study primarily aimed to develop teaching exemplars utilizing creative teaching strategies to enhance pupil achievement and attitude in history. Specifically, the study answered the following questions: (1) What teaching exemplars utilizing creative teaching strategies could be prepared to enhance pupil achievement and attitude in history? (2) Is there a significant difference between the academic achievement of pupils who experienced creative teaching strategies in history from the academic achievement of those who did not? (3) What is the effect of creative teaching strategies on pupil attitude? This study involved two sections of Grade 4 at Placido Del Mundo Elementary School for the School Year 2007-2008. These sections are heterogeneous and were grouped based on their grade averages. Fifty-six pupils (experimental group) were taught using the creative teaching strategies and fifty-three (control group) pupils were taught the conventional way. The instruments used to gather data were a 40-item Achievement Test in Heograpiya, Kasaysayan at Sibika 4, creative lesson exemplars, evaluation instrument for the lesson exemplars, and a survey questionnaire/attitudinaire to determine the attitude of the students exposed to creative teaching strategies. These research instruments were reviewed and evaluated by HKS 4 practitioners and the thesis adviser. The data gathered were analyzed utilizing weighted mean to determine what teaching exemplars could be used and to tell whether or not the implementation of creative teaching strategies has effects on pupil achievement and attitude. The t-test for two independent samples (non-directional) was employed to determine the significance of differences between the test scores of the experimental group and of the control group. Data analysis revealed that (1) the lesson exemplars used in the implementation of creative teaching strategies were rated by evaluators to be "excellent" in terms of objectives, content, learning activities, creative teaching strategies, and evaluation; (2) the result of the posttest shows that there is a significant difference between the test scores of the experimental group and the control group; and (3) the results of the attitudinaire show that the respondents "Strongly Agreed" that creative teaching strategies have positive effects on their attitude. Likewise, they "strongly disagreed" that the implementation of creative teaching strategies has negative effects on their attitude. Based on the foregoing findings of the study, it is concluded that (1) there are teaching exemplars utilizing creative teaching strategies that could be prepared to enhance pupil achievement and attitude; (2) the results of the posttest and attitudinaire show the pupils taught with creative teaching strategies gained more knowledge and positive attitude towards HKS than those who were not. On the basis of the findings and conclusions, it is recommended that (1) in order to ensure the effective transfer of learning, creative teaching strategies shoulc be utilized in the classroom as an alternative teaching methodology specifically in the areas of geography, history, and civics; (2) Social Studies teachers should integrate creative teaching strategies and activities in their day-to-day lessons; (3) Teachers should enhance their creative thinking strategies; (4) Replication of the study in geography, political science, economics and other discipline/fields related to social sciences should be encouraged and pursued; (5) School administators should promote and enhance teachers' knowledge about creativity, creative processes and creative teaching and learning strategies; (6) teachers should develop more instructional materials utilizing varied creative teaching strategies, and; (7) educational institutions should conduct teacher-training programs for Social Studies teachers about creative thinking skills and creative teaching strategies in basic education.